Analisis Kemandirian Belajar Siswa terhadap Hasil Belajar Matematika Kelas XI IPA - ; Santa Aktavia Tara (Jurnal Riset Pendidikan Matematika Jakarta, 2023)
This study aims to analyze student learning independence towards mathematics learning outcomes. The research method used is descriptive qualitative method. The subjects in this study were students of Nusantara Indah Sintang High School with the number of subjects studied being 3 students of class XI IPA. Data collection techniques in the form of interviews and documentation regarding student learning independence towards mathematics learning outcomes. Conclusions were obtained from the results of the analysis based on the 7 indicators of learning independence that the researchers used from several indicators of experts. Based on the data analysis, it can be concluded that the learning independence of students with high mathematics learning achievement categories is already good for independent learning, while those with moderate categories are sufficient for independent learning and the low learning achievement category is less able to learn independently.